The lower energy diffraction and scattering side‐bounce beamline for materials science at the Canadian Light Source. (26th March 2021) - Leontowich, Adam F. G.; Gomez, Ariel; Diaz Moreno, Beatriz; Muir, David; Spasyuk, Denis; King, Graham; Reid, Joel W.; Kim, Chang-Yong; Kycia, Stefan
Abstract : A description of a new hard X‐ray diffraction beamline for materials science at the Canadian Light Source is presented. Abstract : A new diffraction beamline for materials science has been built at the Canadian Light Source synchrotron. The X‐ray source is an in‐vacuum wiggler with a 2.5 T peak magnetic field at 5.2 mm gap. The optical configuration includes a toroidal mirror, a single side‐bounce Bragg monochromator, and a cylindrical mirror, producing a sub‐150 µm vertical × 500 µm horizontal focused beam with a photon energy range of 7–22 keV and a flux of 10 12 photons per second at the sample position. Three endstations are currently open to general users, and the techniques available include high‐resolution powder diffraction, small molecule crystallography, X‐ray reflectivity, in situ rapid thermal annealing, and SAXS/WAXS. The beamline design parameters, calculated and measured performance, and initial experimental results are presented to demonstrate the capabilities for materials science.